Prevalence and determinants of anemia among hospitalized patients: a cross-sectional study - Bahadur Singh, Amresh; Ranjan Gupta, Nitin; Singh, Seema (International Journal of Research in Medical Sciences, 2025)
Background: Anemia is a prevalent comorbidity among hospitalized patients, often exacerbating the burden of underlying chronic illnesses. Understanding its prevalence, severity, and determinants is critical for improving patient care and outcomes. Methods: This cross-sectional study, conducted at two hospitals in Uttar Pradesh, India, investigated anemia among 372 hospitalized patients aged 15 years and above. Sociodemographic, nutritional, and lifestyle factors were recorded using structured questionnaires, and anemia was classified based on WHO hemoglobin thresholds. Morphological subtypes were determined through hematological analysis. Logistic regression analysis identified factors associated with anemia. Results: Anemia prevalence was 64.2%, with moderate anemia being the most common (34.1%), followed by severe (15.3%) and mild anemia (14.8%). Normocytic normochromic anemia (32.8%) was the predominant type, followed by microcytic hypochromic anemia (28.2%). Significant predictors of anemia included daily alcohol consumption (AOR: 3.75, CI: 1.69-8.27), underweight BMI (AOR: 9.23, CI: 2.87-30.23), malnutrition (AOR: 2.59, CI: 1.15-5.83), and chronic kidney disease (AOR: 11.15, CI: 4.06-30.60). Conclusions: Anemia is highly prevalent among hospitalized patients, driven by chronic diseases, malnutrition, and lifestyle factors. Normocytic normochromic anemia was most common, highlighting the contribution of chronic illnesses like kidney and liver diseases. These findings emphasize the need for targeted interventions addressing nutritional support and management of chronic conditions to mitigate anemia’s burden in hospitalized populations.